Double-sided adhesive sheet and laminate for image display device

By developing a baseless double-sided adhesive sheet containing a specific (meth)acrylic acid copolymer, the problem of wrinkles or bubbles caused by repeated bending in the foldable display is solved, and the effect of excellent visual recognition and wrinkles and bubble suppression is achieved.

CN118852998BActive Publication Date: 2025-04-18아티엔스가부시키가이샤 +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410277505.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2024-03-12
Publication Date
2025-04-18
Estimated Expiration
2044-03-12

AI Technical Summary

Technical Problem

When used in flexible optical components such as foldable displays, the existing adhesive layer is prone to wrinkles or bubbles due to repeated bending, which affects adhesion and visual recognition.

Method used

A double-sided adhesive sheet without a substrate is developed, which is made of a first peeling sheet, an adhesive layer and a second peeling sheet. The adhesive layer contains a (meth)acrylic acid copolymer with a weight average molecular weight of 1 million to 1.8 million, and the reflection intensity of the adhesive layer is adjusted by a waveform scanning device to improve visual recognition and suppress the generation of wrinkles and bubbles.

Benefits of technology

It achieves excellent visual recognition in optical and flexible display applications and can effectively suppress the generation of wrinkles and bubbles, especially maintain good performance in the low-temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852998B_ABST
    Figure CN118852998B_ABST
Patent Text Reader

Abstract

The present invention provides a double-sided adhesive sheet without a substrate, which has excellent visibility even when used for optical purposes, and can suppress wrinkles and bubbles even when used for flexible display purposes. The present invention also provides a laminate for an image display device. The double-sided adhesive sheet is a double-sided adhesive sheet without a substrate, which is laminated in the order of a first peeling sheet (1), an adhesive layer (3), and a second peeling sheet (2), wherein when the surface of the adhesive layer (3) is measured using a waveform scanning device, the reflection intensity Wa in the wavelength range of 0.1 mm to 0.3 mm is 1 to 26, and the reflection intensity Wd in the wavelength range of 3 mm to 10 mm is 0.3 to 8. With respect to the adhesive layer (3), it satisfies specific conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a double-sided adhesive sheet and a laminate for an image display device. Background Art

[0002] Adhesive sheets can be joined to adherends by a simple means of attachment, and therefore are often used in electronic devices such as personal computers and smartphones that require various components to be joined to each other, and various proposals have been made. For example, International Publication No. 2011 / 111575 discloses an optical adhesive sheet having an acrylic polymer formed from a monomer having a Tg of -10°C or higher when forming a homopolymer as an essential monomer component, and having a shear storage elastic modulus of 0.8×10 5 Pa~5.0×10 5The acrylic adhesive layer of the present invention has a water content of 0.65 wt % or more after being stored at 60° C. and 95% relative humidity (RH) for 120 hours. In addition, Japanese Patent Laid-Open No. 2013-127012 and Chinese Patent Application Publication No. 104231981 disclose an adhesive, which comprises an acrylic copolymer (A), a polyisocyanate curing agent (B) and a silane coupling agent (C), wherein the acrylic copolymer (A) is obtained by free radical polymerization of 20 wt % to 90 wt % of an ethylenically unsaturated monomer (A1) having an alkyl group with a solubility parameter (SP) value of 8 or more and less than 9.00 and 10 wt % to 80 wt % of an ethylenically unsaturated monomer (A2) having a polar group with an SP value of 9.00 or more and 15 or less. Furthermore, Japanese Patent Laid-Open No. 2014-74122 discloses an adhesive composition containing a (meth)acrylic acid polymer, wherein the (meth)acrylic acid polymer comprises 5% by mass or more of a structural unit (A) derived from an alkyl (meth)acrylate having an alkyl group with at least 12 carbon atoms, 5% by mass or more of a structural unit (B) derived from an alkyl (meth)acrylate having an alkyl group with at least 1 and at most 8 carbon atoms, and 2% by mass or more and 30% by mass or less of a structural unit (C) derived from a monomer having a hydroxyl group, wherein the total content of the structural unit (A), the structural unit (B) and the structural unit (C) is 80% by mass or more. In addition, Japanese Patent Laid-Open No. 2016-188309 discloses an adhesive composition, which includes a (meth) acrylic copolymer having an acid value of 2.5 mgKOH / g or less, a structural unit derived from a monomer including a hydroxyl group in a range of 0.01% to 1% by mass relative to all structural units, a toluene diisocyanate compound in a range of 5 to 30 parts by mass relative to 100 parts by mass of the (meth) acrylic copolymer, and an imidazole compound. Furthermore, Japanese Patent Laid-Open No. 2016-79266 discloses an adhesive composition, which includes a (meth) acrylic polymer having a carboxyl group, and an alicyclic epoxy-modified silicone in an amount of 0.005 to 2.5 parts by mass relative to 100 parts by mass of the (meth) acrylic polymer. In addition, Japanese Patent Publication No. 2018-2961 discloses an adhesive composition, in which the gel fraction just after the adhesive layer is formed is 40% to 80%, and the gel fraction after storage at 23°C and 55% RH for 7 days from the formation of the adhesive layer is 60% to 85%.A laminated sheet is disclosed in Japanese Patent Publication No. 2020-83908, in which, when the reflection intensity (Wb) in a wavelength range of 0.3 mm to 1.0 mm is measured on the exposed surface of the release film using a waveform scanning device, the reflection intensity (Wb) is less than 10.0, and Japanese Patent Publication No. 2020-83910 is disclosed, in which the thickness of the film substrate is less than 38 μm, and when the reflection intensity (Wb) in a wavelength range of 0.3 mm to 1.0 mm is measured on the exposed surface of the release film using a waveform scanning device, the reflection intensity (Wb) is greater than 10, and the adhesive layer contains at least a structure derived from a (meth)acrylic acid copolymer and a chelating crosslinking agent. Summary of the invention

[0003] [Problems to be solved by the invention]

[0004] As described above, the adhesive layer can be used to join adherends to each other using a simple method, so it is often used in electronic devices. However, regarding the adhesive layer, it cannot be said that the repeated bending tolerance is high. For example, in the case of foldable foldable display applications that have rapidly become popular in recent years, there is a problem of easily generating wrinkles or bubbles over time. The generation of such wrinkles or bubbles will not only reduce the adhesion, but also cause the visibility of the surface protective film to be reduced, so it is particularly serious in the case of optical components such as displays.

[0005] In the market, a double-sided adhesive sheet without a substrate is sought in terms of productivity, versatility, and the need for thinning and miniaturization of various electronic devices. In addition, an adhesive layer with excellent visibility that can suppress wrinkles or bubbles over time is sought even when applied to applications requiring flexibility such as foldable displays. In particular, it is desired to develop an adhesive layer that can suppress the generation of wrinkles or bubbles from low temperature (0°C) to high temperature (40°C).

[0006] Furthermore, in the above description, the problems of the adhesive layer used for display applications are described, but similar problems may occur in all applications where visibility is to be improved.

[0007] The present disclosure has been made in view of the above problems, and an object of the present disclosure is to provide a substrate-less double-sided pressure-sensitive adhesive sheet which has excellent visibility even when used for optical applications and can suppress wrinkles and bubbles even when used for flexible displays.

[0008] [Technical means to solve the problem]

[0009] The present disclosure provides the following double-sided adhesive sheet and laminated body for image display devices.

[0010] [1]: A double-sided adhesive sheet for use in a substrate-free flexible display, wherein a first release sheet, an adhesive layer, and a second release sheet are laminated in this order, wherein:

[0011] When a glass substrate is attached to the surface of the adhesive layer exposed by peeling off the first peeling sheet and the glass substrate is placed on a white paper, the surface of the adhesive layer exposed by peeling off the second peeling sheet is measured by a waveform scanning device.

[0012] The reflection intensity Wa in the wavelength range of 0.1 mm to 0.3 mm is 1 to 26, and

[0013] The reflection intensity Wd in the wavelength range of 3mm to 10mm is 0.3 to 8.

[0014] Regarding the adhesive layer,

[0015] (i) is any one of an adhesive layer containing a (meth)acrylic copolymer (a) having a weight average molecular weight of 1,000,000 to 1,800,000, and an adhesive layer obtained by crosslinking an adhesive composition containing a (meth)acrylic copolymer (a),

[0016] (ii) The storage elastic modulus at 23°C is 1×10 3 Pa~8×10 4 Pa,

[0017] (iii) The glass transition temperature based on differential scanning calorimetry (DSC) is -70°C ≤ Tg ≤ -35°C.

[0018] [2]: The double-sided adhesive sheet according to [1], wherein after a glass substrate is attached to the surface of the adhesive layer exposed by peeling off the first release sheet and the glass substrate is placed on a white paper, the surface of the adhesive layer exposed by peeling off the second release sheet is measured by a waveform scanning device.

[0019] The reflection intensity Wc in the wavelength range of 1mm to 3mm is 1 to 12, and

[0020] The reflection intensity We in the wavelength range of 10 mm to 30 mm is 1 to 12.

[0021] [3]: The double-sided adhesive sheet according to [1] or [2], wherein the (meth)acrylic copolymer (a) comprises structural units derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 6 carbon atoms, and structural units derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 7 to 12 carbon atoms.

[0022] [4]: The double-sided adhesive sheet according to any one of [1] to [3], wherein the molecular weight distribution Mw / Mn of the (meth)acrylic copolymer (a) is less than 5.

[0023] [5]: A laminate for an image display device, wherein adherends are bonded together via the adhesive layer of the double-sided adhesive sheet according to any one of [1] to [4].

[0024] [Effects of the Invention]

[0025] The present disclosure has the excellent effect of providing a substrate-less double-sided pressure-sensitive adhesive sheet that has excellent visibility even when used for optical applications and can suppress wrinkles and bubbles even when used for flexible displays. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic cross-sectional view showing an example of a double-sided adhesive sheet according to an embodiment.

[0027] Figure 2 This is a cross-sectional view for explaining a method of measuring the surface of an adhesive layer using a waveform scanning device.

[0028] [Explanation of Symbols]

[0029] 1: First peeling sheet

[0030] 2: Second peeling sheet

[0031] 3: Adhesive layer

[0032] 4: Glass substrate

[0033] 5: Blank paper

[0034] 10: Double-sided adhesive sheet

[0035] 31, 32: Surface

[0036] w: eaves (area where the adhesive layer 3 is not formed)

[0037] X, Y, Z: direction DETAILED DESCRIPTION

[0038] Hereinafter, the present disclosure will be described in detail. In addition, as long as it conforms to the main purpose of the present disclosure, other embodiments are of course also included in the scope of the present disclosure. In addition, the numerical range determined by using "to" in this specification includes the numerical values ​​recorded before and after "to" as the range of the lower limit and upper limit. In addition, "film", "sheet" and "belt" are synonymous and are not distinguished according to thickness or shape. The so-called (meth)acrylic acid refers to at least one of acrylic acid and methacrylic acid, and the so-called (meth)acrylic acid alkyl ester refers to at least one of acrylic acid alkyl ester and methacrylate alkyl ester. In addition, with respect to various components, as long as there is no special annotation, they can be used independently alone, or two or more can be used in combination. The numerical values ​​in the specification of this case refer to the values ​​obtained by the method described in the embodiments described later.

[0039] 1. Double-sided adhesive sheet

[0040] The double-sided adhesive sheet disclosed herein (hereinafter also referred to as the present adhesive sheet) is a sheet without a substrate formed by stacking a first release sheet, an adhesive layer and a second release sheet in sequence. The present adhesive sheet can be applied to the bonding of various adherends. The present adhesive sheet has excellent visibility and is therefore particularly suitable for optical applications. In addition, the present adhesive sheet can suppress wrinkles and bubbles and is therefore suitable for use as a flexible display. In particular, the repeated durability of folding is excellent and is therefore suitable for use in foldable displays.

[0041] Figure 1 A schematic cross-sectional view of an example of a double-sided adhesive sheet without a substrate according to the present embodiment is shown in FIG. The double-sided adhesive sheet 10 is a sheet without a substrate in which the adhesive layer 3 is sandwiched between a first peeling sheet 1 and a second peeling sheet 2. From the perspective of peeling balance, the following form is preferred: Figure 1 As shown, in the long side direction (Z direction in the figure) of both ends of the adhesive sheet 10 in the width direction (X direction in the figure), the first peeling sheet 1 and the second peeling sheet 2 have eaves w (areas w having non-formed areas of the adhesive layer 3) relative to the adhesive layer 3.

[0042] The degree of unevenness, such as undulation, wave, and orange peel, on the surface of the adhesive layer 3 can be confirmed by a waveform scanning device. The reflection intensity Wa in the wavelength range of 0.1mm to 0.3mm obtained by the waveform scanning device is an indicator of the fine structure that can be seen from a close distance of about 40cm, and usually takes a value of 0 to 80. Among them, in order to prevent the reduction of gloss and blurring, the reflection intensity Wa is preferably in the range of 0 to 1. The reflection intensity Wd in the wavelength range of 3mm to 10mm obtained by the waveform scanning device is an indicator of the fine structure that can be seen from a medium distance of about 3m, and usually takes a value of 0 to 50. Among them, in order to prevent the reduction of adhesion due to the reduction of smoothness, the reflection intensity Wd is preferably in the range of 8 to 30.

[0043] In addition, the reflection intensity Wa, the reflection intensity Wd and the reflection intensity Wb, the reflection intensity Wc, and the reflection intensity We described later are measured by the following operation: on the surface 31 of the adhesive layer 3 exposed by peeling off the first peeling sheet 1, Figure 2 As shown in the figure, the glass substrate 4 is attached and the glass substrate 4 is placed on a white paper 5. Then, the surface 32 of the adhesive layer 3 exposed by peeling off the second release sheet 2 is measured by a waveform scanning device.

[0044] The inventors have repeatedly studied double-sided adhesive sheets without substrates, and as a result, it is known that the following double-sided adhesive sheet without substrate can be obtained, which has excellent visibility even when applied to optical applications by setting the reflection intensity Wa of the surface 32 of the adhesive layer 3 to 1 to 26 and the reflection intensity Wd to 0.3 to 8, and can also suppress the generation of bubbles and wrinkles even when applied to flexible display applications. Although the reason does not deviate from the scope of speculation, it can be considered that by setting the small undulation Wa to the above range and the relatively large undulation Wd to the above range, the adhesion with the adherend can be improved.

[0045] The value of Wa can be adjusted mainly by the coating process. Specifically, it can be adjusted by the solid content concentration when the adhesive composition is applied as a sheet. As the solid content concentration decreases, Wa is in a tendency to become smaller (as the solid content concentration becomes higher, Wa tends to become larger). In addition, the value of Wa can be adjusted by the coating speed of the adhesive composition. As the coating speed becomes faster, Wa tends to become larger. In addition, the value of Wa can be adjusted by the drying conditions (temperature, time, air volume, etc.) when the adhesive composition for forming a sheet is applied. As the drying temperature becomes higher, Wa tends to become larger. In addition, as the drying time becomes longer, Wa tends to become larger. In addition, by adjusting the drying air volume, Wa changes. And then, Wa can also be adjusted according to the aging conditions (time, temperature) after being formed into a sheet. In addition, Wa can also be adjusted according to the film thickness, and is in a tendency to become larger as the film thickness becomes thinner.

[0046] As a method for adjusting Wd, the same method as Wa can be cited. Among them, Wd tends to increase by increasing the drying temperature (and tends to decrease by lowering the drying temperature). In addition, Wd tends to increase by extending the drying time.

[0047] A more suitable range of Wa is 3 to 24, a further suitable range is 4 to 23, and a particularly suitable range is 7 to 19. Moreover, a more suitable range of Wd is 0.5 to 5, a further suitable range is 0.8 to 5, and a particularly suitable range is 1 to 4.

[0048] From the viewpoint of improving visibility, it is preferable to use a waveform scanning device to scan the image on the basis of satisfying the Wa within the specific range and the Wd within the specific range. Figure 2 The reflection intensity Wc of the wavelength region 1mm to 3mm measured on the surface 32 of the adhesive layer 3 shown is 1 to 12, and the reflection intensity We of the wavelength region 10mm to 30mm is 1 to 12. Wc is an indicator of a fine structure that can be seen from a close distance to a medium distance of about 40cm to 3m. By combining the Wc in the Wa and Wd in the specific range, the haze reduction effect becomes even better. By combining the Wa, Wd, and Wc in the specific range and further setting We to the range, the effect of reducing the brightness difference becomes even better. In addition, We is an indicator of a fine structure that can be seen from a long distance of more than 3m.

[0049] As a method for adjusting Wc, the same method as Wa can be cited. Among them, a method for adjusting the solid content concentration and / or the film thickness is suitable. As the solid content concentration increases, Wc tends to increase (as the solid content concentration decreases, Wc tends to decrease).

[0050] In addition, as a method for adjusting We, the same method as the above-mentioned Wa can be cited. Among them, the method of adjusting according to the aging conditions (time, temperature) after the sheet is formed is suitable. As the aging temperature increases, We tends to increase (and as the aging temperature decreases, We tends to decrease).

[0051] A more suitable range of Wc is 2 to 11, and a further suitable range is 2 to 7. Moreover, a more suitable range of We is 1 to 9, and a further suitable range is 1 to 7.

[0052] From the viewpoint of viscosity, the reflection intensity Wb in the wavelength region of 0.3 mm to 1.0 mm is preferably set in the range of 2 to 30. In addition, the viscosity mentioned here is an index of viscosity obtained by the J.Dow method in accordance with Japanese Industrial Standards (JIS) Z-0237:2022. A more preferred Wb is 6 to 30, and a further preferred Wb is 9 to 25. When adjusting Wb, a method of adjusting the coating speed is suitable. As the coating speed increases, Wb tends to increase (as the coating speed decreases, Wb tends to decrease).

[0053] From the viewpoint of improving productivity, the present adhesive sheet is preferably produced in the state of a roll sheet having a long double-sided adhesive sheet wound around a core. For example, a roll sheet is obtained by winding a long double-sided adhesive sheet around a cylindrical core having an outer diameter (diameter) of about 100 mm to 1000 mm. The width of the double-sided adhesive sheet is, for example, 100 mm to 3000 mm, and the winding length of the adhesive sheet is, for example, 10 m to 3000 m. In the case of a roll sheet, the present adhesive sheet is rolled out and cut and / or punched when shipped or used. Then, after the first release sheet 1 is peeled off and removed, the exposed adhesive layer 3 is attached to the adherend, and then the second release sheet 2 is peeled off and removed, and the adhesive layer 3 thus exposed is attached to other adherends. Through this process, the adherends are joined to each other.

[0054] 2. Adhesive layer

[0055] The adhesive layer is a layer formed of an adhesive composition. The adhesive composition is a cross-linked adhesive or a non-cross-linked adhesive, and may be any of an emulsion type, a solvent type, and a solvent-free type.

[0056] The present adhesive layer has Wa within the specific range and Wd within the specific range, and satisfies the following (i) to (iii).

[0057] (i) An adhesive layer containing a (meth)acrylic copolymer (a) having a weight average molecular weight of 1,000,000 to 1,800,000 (an adhesive layer comprising a non-crosslinked adhesive), or an adhesive layer obtained by crosslinking an adhesive composition containing a (meth)acrylic copolymer (a) (an adhesive layer obtained by crosslinking a crosslinked adhesive).

[0058] (ii) The storage elastic modulus at 23°C is 1×10 3 Pa~8×10 4 Pa.

[0059] (iii) The glass transition temperature determined by DSC is -70°C ≤ Tg ≤ -35°C.

[0060] According to the adhesive layer, for example, in the stage of a roll-shaped double-sided adhesive sheet (first release sheet / adhesive layer / second release sheet), the deformation of the adhesive layer can be effectively suppressed. In addition, according to the adhesive layer, it can withstand repeated bending and exhibit an excellent recovery rate when returning from a bent state to an original state. Regarding the time-dependent suppression effect of bubbles and wrinkles, not only an excellent effect is obtained at room temperature (23°C), but also bubbles and wrinkles can be suppressed in a range from low temperature (0°C) to high temperature (40°C).

[0061] The more preferred range of the storage elastic modulus at 23°C is 3×10 3 Pa~7×10 4Pa, and the preferred range is 1×10 4 Pa~5×10 4 In particular, it is believed that by using an adhesive layer having a storage elastic modulus satisfying the above (ii), the deviation that causes bubbles and wrinkles can be absorbed in the concave and convex parts of the adhesive layer, thereby suppressing the generation of bubbles and wrinkles. Therefore, it is particularly suitable for flexible display applications such as foldable displays.

[0062] Regarding the adhesive layer that satisfies the above (i), in other words, the adhesive layer contains a (meth)acrylic copolymer (a) as an adhesive resin, or contains a cross-linked (meth)acrylic copolymer (a). The cross-linking may be the cross-linking of the (meth)acrylic copolymers (a) with each other, or the cross-linking of the (meth)acrylic copolymer (a) and a hardener. From the perspective of obtaining an adhesive layer having both adhesion and cohesion, an adhesive layer having a cross-linked structure of a (meth)acrylic copolymer (a) and a hardener is suitable. By preparing an adhesive layer of (i) containing the (meth)acrylic copolymer component in combination in (ii) and (iii) on the basis of Wa and Wd in the specific range, not only adhesion and bendability can be obtained, but also excellent transparency can be obtained.

[0063] Furthermore, by combining (iii) in which the glass transition temperature based on DSC is -70°C ≤ Tg ≤ -35°C, Wa and Wd in the specific range, and (i) and (ii) to form an adhesive layer, excellent flexibility can be exerted. As a result, an adhesive layer that can suppress wrinkles and bubbles even when applied to flexible displays can be obtained. A more preferred range is -65°C ≤ Tg (DSC) ≤ -50°C, and a further preferred range is -65°C ≤ Tg (DSC) ≤ -55°C.

[0064] From the viewpoint of bubbles and wrinkles in folding under low temperature (0°C) conditions, the storage elastic modulus of the adhesive layer at 0°C and a frequency of 1 Hz is preferably 2×10 3 Pa~1.5×10 5 Pa, more preferably 1×10 4 Pa~1.4×10 5 Pa, and more preferably 1.2×10 4 Pa~9×10 4 Pa.

[0065] In addition, from the viewpoint of bubbles and wrinkles in folding under high temperature (40°C) conditions, the storage elastic modulus of the adhesive layer at 40°C and a frequency of 1 Hz is preferably 8×10 2 Pa~7×10 4 Pa, more preferably 1×10 3 Pa~5.5×10 4Pa, and more preferably 8×10 3 Pa~5×10 4 Pa.

[0066] The thickness Ta of the adhesive layer is arbitrary. From the perspective of maintaining good light transmittance, bendability and surface structure while exerting adhesive force, the thickness Ta of the adhesive layer is preferably about 5 μm to 150 μm. The thickness Ta of the adhesive layer is more preferably in the range of 15 μm to 120 μm, and further preferably in the range of 25 μm to 100 μm. In addition, the thickness Ta of the adhesive layer is obtained by the method of the embodiments described later.

[0067] The adhesive force of the adhesive layer can be arbitrarily designed according to the purpose. The adhesive force of the adhesive layer can be controlled by the composition of the adhesive resin constituting the adhesive composition described later, the Tg of the adhesive resin, the amount of the hardener in the adhesive composition, etc. The adhesive force is improved by using a (meth) acrylic acid copolymer (a) obtained by using a high-polarity (meth) acrylic acid monomer ((meth) acrylic acid monomer) derived from a carboxyl-containing monomer as a monomer. The lower the Tg of the adhesive resin, the higher the adhesive force tends to be. Furthermore, the less the amount of the hardener in the adhesive composition, the higher the adhesive force tends to be.

[0068] In terms of effectively preventing cohesive failure and effectively suppressing dents in the double-sided adhesive sheet, the adhesive layer can also be a layer with a sea island type microphase separation structure, and the sea island type microphase separation structure includes a continuous phase containing a soft segment and a dispersed phase containing a hard segment. The adhesive layer is preferably dispersed with a structure of a dispersed phase containing a hard segment in a matrix forming a continuous phase containing a soft segment. The microphase separation structure can be confirmed by an atomic force microscope (Atomic Force Microscope, AFM), a transmission electron microscope (Transmission Electron Microscope, TEM), a scanning probe microscope (Scanning Probe Microscope, SPM), etc. By forming a microphase separation structure, a kind of adhesive layer that gives excellent elasticity and can effectively suppress the generation of cracks can be provided.

[0069] From the viewpoint of folded bubbles and wrinkles, the gel fraction of the adhesive layer is preferably 70% to 90%. The gel fraction is obtained by the method described in the examples described below. The gel fraction is more preferably 75% to 90%, and further preferably 75% to 85%.

[0070] 2-1. Adhesive resin

[0071] As the adhesive resin, as described above, a (meth)acrylic copolymer (a) having a weight average molecular weight (Mw) of 1 million to 1.8 million is used. By using a (meth)acrylic copolymer (a) in the above range, not only is the strength excellent, but also excellent extraction processability can be obtained. The lower limit of the Mw of the (meth)acrylic copolymer (a) is more preferably 1.1 million. In addition, the upper limit of the Mw is more preferably 1.7 million, further preferably 1.5 million, and particularly preferably 1.3 million. In addition, from the viewpoint of suppressing bubbles and wrinkles that change over time when folding in the region from low temperature (0°C) to high temperature (40°C), the molecular weight dispersion Mw / Mn of the (meth)acrylic copolymer (a) is preferably less than 5. It is more preferably 2 to 4.5, and more preferably 2.5 to 4.

[0072] The (meth)acrylic acid copolymer (a) preferably contains (meth)acrylic acid ester as a monomer. As a suitable example of (meth)acrylic acid ester, an alkyl (meth)acrylic acid ester monomer can be exemplified. When forming a cross-linked adhesive, it is preferably a (meth)acrylic acid copolymer obtained by copolymerizing a functional group-containing monomer with a (meth)acrylic acid ester.

[0073] The alkyl group of the (meth)acrylic acid alkyl ester may be a linear or branched chain. The alkyl group is preferably an alkyl group having 1 to 20 carbon atoms, and more preferably an alkyl group having 1 to 12 carbon atoms. Specific examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and lauryl (meth)acrylate.

[0074] The (meth)acrylic acid copolymer (a) preferably has a structural unit derived from a chain or branched (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with a carbon number of 1 to 6, and a structural unit derived from a chain or branched (meth)acrylic acid alkyl ester monomer (a-2) having an alkyl group with a carbon number of 7 to 12. By including one or more structural units derived from a chain or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with a carbon number of 1 to 6, it is easy to show interaction with the adherend interface within a short contact time, thereby improving the adhesion. In addition, by including one or more structural units derived from a chain or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with a carbon number of 7 to 12, it is easy to wet and spread on the adherend interface within a long contact time, thereby improving the adhesion.

[0075] As a more preferred embodiment of the (meth)acrylic acid copolymer (a), there can be mentioned a combination of one or more structural units derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 4 carbon atoms and one or more structural units derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 8 to 12 carbon atoms. As a suitable combination, there can be mentioned any combination selected from methyl (meth)acrylate and n-butyl (meth)acrylate as (a-1), and 2-ethylhexyl (meth)acrylate and dodecyl (meth)acrylate as (a-2).

[0076] The content of the structural unit derived from the (meth)acrylic acid alkyl ester containing a linear or branched alkyl group is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass, based on 100% by mass of the (meth)acrylic copolymer (a).

[0077] As the monomer used in the (meth)acrylic acid copolymer (a), a (meth)acrylic acid alkyl ester monomer (a-3) whose alkyl group is cyclic is also suitable. Examples of such monomers include cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Among these, cyclohexyl (meth)acrylate and isobornyl (meth)acrylate are particularly preferred from the viewpoint of bendability and adhesiveness.

[0078] From the perspective of more effectively exerting bubbles and wrinkles during folding under low temperature, room temperature and high temperature conditions, the ratio (a-2) / (a-1) of the single body (a-2) to the single body (a-1) is preferably 0.9 to 20, more preferably 1 to 20, further preferably 3 to 20, and particularly preferably 4 to 20.

[0079] In terms of the recovery rate, it is suitable to use a linear or branched (meth)acrylic acid alkyl ester with 12 carbon atoms in the alkyl group in monomer (a-2) in combination with monomer (a-1). Further, in terms of the recovery rate, it is more suitable to use monomer (a-3) in addition to using a linear or branched (meth)acrylic acid alkyl ester monomer (a-1) with 1 to 6 carbon atoms in the alkyl group and a linear or branched (meth)acrylic acid alkyl ester monomer (a-2) with 8 to 12 carbon atoms in the alkyl group.

[0080] Examples of the functional group-containing monomer include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an epoxy group-containing monomer, and an amino group-containing monomer. By containing the functional group-containing monomer, the cohesion of the adhesive is improved, and a tough adhesive layer can be obtained.

[0081] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, β-carboxyethyl (meth)acrylate, p-carboxybenzyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, and isocrotonic acid. Among these, (meth)acrylic acid is preferred in terms of cohesion and adhesiveness.

[0082] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate are more preferred in terms of cohesion and adhesiveness.

[0083] Examples of the epoxy group-containing monomer include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate.

[0084] Examples of the amino group-containing monomer include (meth)acrylic acid monoalkylamino esters such as monoethylaminoethyl (meth)acrylate, monoethylaminopropyl (meth)acrylate, monomethylaminoethyl (meth)acrylate, and monomethylaminopropyl (meth)acrylate.

[0085] In terms of tackiness, the Tg (DSC) of the (meth)acrylic acid copolymer (a) is preferably -70°C < Tg < -35°C. More preferably, it is -65°C to -40°C, and still more preferably, it is -65°C to -50°C.

[0086] The total amount of the structural units derived from the functional group-containing monomer is preferably 1 to 20% by mass relative to 100% by mass of the (meth)acrylic copolymer (a). By setting the content within the above range, the cohesive force can be adjusted by reaction with the curing agent, and the flexibility and recovery rate can be improved.

[0087] Relative to 100% by mass of the (meth) acrylic copolymer (a), the structural unit derived from the monomer containing a carboxyl group is preferably 1% to 10% by mass. By being within the range, the cohesive force and relaxation of the adhesive layer can be taken into account. In addition, relative to 100% by mass of the (meth) acrylic copolymer (a), the structural unit derived from the monomer containing a hydroxyl group is preferably 1% to 10% by mass. By being within the range, the adhesion and heat resistance of the adhesive layer can be taken into account.

[0088] The (meth)acrylic acid copolymer (a) may contain structural units derived from other monomers that can be copolymerized with the monomers. Examples of other monomers include monomers having an alkylene oxide group and other vinyl monomers. In addition, examples include: methoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, vinyl acetate, vinyl crotonate, styrene, acrylonitrile, and acrylamide. In 100% by mass of the (meth)acrylic acid copolymer (a), the structural units derived from other monomers are preferably 0.1% by mass to 20% by mass.

[0089] The (meth)acrylic acid copolymer (a) is obtained by polymerizing a monomer mixture. During the polymerization, a polymerization initiator is used as needed. The polymerization initiator is preferably a free radical polymerization initiator. As free radical polymerization initiators, peroxides and azo compounds are suitable. Examples of azo compounds include: 2,2'-azobisisobutyronitrile (abbreviation: AIBN (2,2'-azobisisobutyronitrile)), 2,2'-azobis(2-methylbutyronitrile) and other 2,2'-azobisbutyronitrile; 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitrile such as 2,2'-azobis(2-hydroxymethylpropionitrile); 1,1'-azobis-1-alkanenitrile such as 1,1'-azobis(cyclohexane-1-carbonitrile). Examples of peroxides include dialkyl peroxides such as di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl isopropyl peroxide, α,α'-bis(tert-butylperoxy-m-isopropyl)benzene, and 2,5-di(tert-butylperoxy)hexyne-3-ol; peroxyesters such as tert-butyl peroxybenzoate, tert-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; 2,2-bis(4,4-di-tert-butylperoxycyclohexanone); Peroxyketals such as 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and n-butyl-4,4-bis(tert-butylperoxy)valerate; hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; and peroxydicarbonates such as bis(tert-butylcyclohexyl)peroxydicarbonate. The content of the polymerization initiator is, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of the monomer mixture.

[0090] The polymerization method is not limited. For example, polymerization can be carried out by solution polymerization, bulk polymerization, emulsion polymerization and suspension polymerization. Examples of solvents used in solution polymerization include acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone and cyclohexanone. The polymerization temperature is, for example, 60° C. to 120° C., and the polymerization time is about 2 hours to 12 hours.

[0091] As the adhesive resin, other resins other than the (meth)acrylic acid copolymer (a) may be contained within the scope of the present disclosure. As other resins, rubber resins, silicone resins, urethane resins, polyamide resins, polyimide resins, polyester resins, and fluororesins may be exemplified. These resins may be used alone or in combination of two or more.

[0092] 2-2. Hardener

[0093] As described above, the adhesive composition may include a hardener. As a hardener, for example, isocyanate compounds, epoxy compounds, aziridine compounds, carbodiimide compounds, metal chelates, etc. can be cited. The hardener may be a low molecular compound or a polymer compound. When the functional group is a hydroxyl group or a carboxyl group, isocyanate compounds and epoxy compounds are preferred. Among these, isocyanate compounds are preferred in terms of the viewpoint that high cohesion and adhesion can coexist.

[0094] Among isocyanate curing agents, aromatic isocyanates are more preferred. By using an adhesive composition comprising a (meth)acrylic copolymer (a) and an aromatic isocyanate curing agent, a more excellent recovery rate can be obtained. From the perspective of compatibility between the (meth)acrylic copolymer (a) and the curing agent, an isocyanate curing agent (b) having an aromatic ring such as an aromatic polyisocyanate or an aromatic aliphatic polyisocyanate is preferred.

[0095] The isocyanate compound is an isocyanate having two or more isocyanate groups and is preferably an isocyanate monomer such as aromatic polyisocyanate, aliphatic polyisocyanate, aromatic aliphatic polyisocyanate, alicyclic polyisocyanate, and a biuret form, urate form, and adduct thereof.

[0096] Examples of the aromatic polyisocyanate include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0097] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI (hexamethylene diisocyanate)), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0098] Examples of the aromatic aliphatic polyisocyanate include ω,ω′-diisocyanate-1,3-dimethylbenzene, ω,ω′-diisocyanate-1,4-dimethylbenzene, ω,ω′-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0099] Examples of the alicyclic polyisocyanate include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI (isophorone diisocyanate), isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanate methyl)cyclohexane.

[0100] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer. Examples of the biuret form include a biuret form of hexamethylene diisocyanate.

[0101] The urate body is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of toluene diisocyanate.

[0102] The adduct is a difunctional or higher isocyanate compound formed by reacting an isocyanate monomer with a difunctional or higher compound containing low molecular active hydrogen. Examples of the adduct include a compound formed by reacting trimethylolpropane with hexamethylene diisocyanate, a compound formed by reacting trimethylolpropane with toluene diisocyanate, a compound formed by reacting trimethylolpropane with xylylene diisocyanate, a compound formed by reacting trimethylolpropane with isophorone diisocyanate, and a compound formed by reacting 1,6-hexanediol with hexamethylene diisocyanate.

[0103] From the viewpoint of forming a sufficient cross-linked structure, the isocyanate compound is preferably a trifunctional isocyanate compound. The isocyanate compound is more preferably an adduct of a reaction product of an isocyanate monomer and a trifunctional compound containing low molecular active hydrogen, and a urate body. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a urate body of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, a urate body of toluene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, and a urate body of isophorone diisocyanate, more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate.

[0104] Examples of the epoxy compound include glycerol diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0105] Examples of the aziridine compound include N,N′-diphenylmethane-4,4′-bis(1-aziridineamide), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4′-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0106] The carbodiimide compound is preferably a high molecular weight polycarbodiimide generated by subjecting a diisocyanate compound to a decarbonation condensation reaction in the presence of a carbodiimidization catalyst. The commercially available product of the high molecular weight polycarbodiimide is preferably the Carbodilite series of Nissinbo Co., Ltd. Among them, Carbodilite V-03, 07, and 09 are preferably preferred due to their excellent compatibility with organic solvents.

[0107] The metal chelate is preferably a coordination compound of a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or ethyl acetylacetate. Examples of the metal chelate include ethyl acetylacetate aluminum-diisopropyl alcohol ester, aluminum triacetylacetonate, bisethyl acetylacetate aluminum-monoacetylacetonate, and alkyl acetylacetate aluminum-diisopropyl alcohol ester.

[0108] The curing agent is preferably contained in an amount of 0.001 to 1 part by mass, more preferably 0.01 to 0.1 part by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (a). When the content is 0.001 parts by mass or more, the cohesive force is further improved, and when the content is 1 part by mass or less, it is easy to achieve both cohesive force and flexibility, which is preferred.

[0109] 2-3. Hard segment

[0110] This adhesive composition may also add a hard segment as needed to form an island-type microphase separation structure in the adhesive layer. The hard segment comprises a non-crosslinked beaded particle having a higher Tg than the soft segment. As beaded particles, for example, (meth) acrylic resin, polystyrene resin, polyethylene resin, epoxy resin, silicone resin can be exemplified. It is preferably a resin having excellent compatibility with the adhesive resin. From the above point of view, it is suitable to use the same resin. From the point of view of compatibility, for the (meth) acrylic copolymer (a) as the soft segment, the hard segment is also preferably a combination of (meth) acrylic resins.

[0111] 2-4. Other additives

[0112] The adhesive composition may further contain a solvent, a tackifier, a silane coupling agent, a filler, a colorant, an antioxidant, an antistatic agent, an ultraviolet absorber, etc. as necessary.

[0113] Examples of the solvent include esters such as ethyl acetate, propyl acetate, and butyl acetate; and ketones such as acetone, methyl ethyl ketone, and cyclohexanone. In addition, examples include aromatic hydrocarbons such as toluene, xylene, benzene, and solvent naphtha; and aliphatic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, ethylcyclohexane, diethylcyclohexane, decahydronaphthalene, bicycloheptane, tricyclodecane, hexahydroindenylcyclohexane, cyclooctane, α-pinene, terpinolene, and limonene. The solvent may be used alone or in combination.

[0114] As the adhesion imparting agent, adhesive compounds with a weight average molecular weight of less than 10,000 can be cited. For example, rosin resin, polymerized rosin resin, rosin ester resin, polymerized rosin ester resin, terpene resin, terpene phenol resin, coumarone resin, coumarone indene resin, styrene resin, xylene resin, phenol resin, petroleum resin, etc. can be cited. Among these, rosin resin, polymerized rosin resin, rosin ester resin and polymerized rosin ester resin are preferred in terms of good compatibility with (meth) acrylic copolymer (a) and further improved adhesion performance, and rosin ester resin and polymerized rosin ester resin are more preferred. Relative to 100 parts by mass of (meth) acrylic copolymer (a), the adhesion imparting resin is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.5 to 7 parts by mass. If 0.01 to 10 parts by mass of adhesion imparting resin are used, high adhesion can be obtained.

[0115] Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloxy group such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane;

[0116] Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane;

[0117] Alkoxysilane compounds having an amino group such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane;

[0118] Alkoxysilane compounds having a mercapto group such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane;

[0119] Alkoxysilane compounds having an epoxy group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane;

[0120] Tetraalkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane;

[0121] 3-Chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, silicone resin having an alkoxysilyl group in the molecule, and the like.

[0122] The silane coupling agent is used in an amount of preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the (meth)acrylic copolymer (a).

[0123] By adding a filler, optical and mechanical properties can be adjusted. Examples of the filler include inorganic white pigments such as silicon dioxide, calcium carbonate, aluminum hydroxide, magnesium hydroxide, clay, talc, and titanium dioxide.

[0124] 3. First peeling sheet and second peeling sheet

[0125] The adhesive layer is sandwiched between the first release sheet and the second release sheet. Wa to We of the adhesive layer are also affected by the type of the release sheet of the adhesive layer, especially the type of the release layer of the second release sheet.

[0126] The peeling force of the first peeling sheet 1 and the second peeling sheet 2 can be adjusted by the demoulding treatment of the surface of each peeling sheet attached to the adhesive layer. For example, the peeling force can be adjusted according to the type of the release agent. In addition, the peeling force can be adjusted according to the coating amount of the release agent. And then, it can be adjusted according to the surface roughness of the release layer. In addition, it can also be adjusted by the adhesive composition forming the adhesive layer. In the case of improving the peeling force, it is effective to make the surface roughness smooth, increase the coating amount of the release agent, etc., and in the case of weakening the peeling force, as long as the opposite is adjusted.

[0127] The first release sheet and the second release sheet can be arbitrarily selected, and the same release sheet can also be used. From the viewpoint of processability, it is preferable that the first release sheet is a light release sheet and the second release sheet is a heavy release sheet. It is preferable that the thickness Tl of the light release sheet is in the range of 25 μm to 100 μm, the thickness of the heavy release sheet is in the range of 50 μm to 188 μm, and the relationship Tl < Th is satisfied. In addition, when forming an adhesive sheet roll, it is preferable to dispose the light release sheet on the outer side of the roll.

[0128] In an environment of 23°C and a relative humidity of 50%, the peeling force Pl when peeling the first release sheet from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min can be appropriately adjusted. However, from the viewpoint of effectively suppressing tunneling phenomena such as the floating and partial peeling of the adhesive layer, it is preferably set to 0.02 N / 25 mm to 0.30 N / 25 mm. In addition, from the viewpoint of effectively suppressing the phenomenon of forced separation between the adhesive layer and the second release sheet, it is preferable that after peeling the first release sheet from the adhesive layer, in an environment of 23°C and a relative humidity of 50%, when further peeling the second release sheet from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min, the peeling force Ph is set to 0.10 N / 25 mm to 0.80 N / 25 mm within the range where Ph / Pl satisfies 2 to 6 in relation to the peeling force Pl.

[0129] Examples of the first release sheet and the second release sheet include: polyethylene sheet, polypropylene sheet, polybutene sheet, polybutadiene sheet, polymethylpentene sheet, polyvinyl chloride sheet, vinyl chloride copolymer sheet, polyethylene terephthalate sheet, polyethylene naphthalate sheet, polybutylene terephthalate sheet, polyurethane sheet, ethylene vinyl acetate sheet, ionomer resin sheet, ethylene-(meth)acrylic acid copolymer sheet, ethylene-(meth)acrylate copolymer sheet, polystyrene sheet, polycarbonate sheet, polyimide sheet, fluororesin sheet. The first release sheet can be a single layer or a laminate.

[0130] In addition to using a sheet having releasability by itself for the first release sheet 1 and / or the second release sheet 2, releasability can also be imparted by coating a release agent on the joint surface with the adhesive layer 3. There is a method of coating a release agent such as an alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, or wax-based release agent as the release agent. The peeling force can be adjusted by changing the type of the release agent.

[0131] The method for forming the release layer is preferably a method of forming the release layer by coating a release agent composition on a release substrate. The release agent may contain a solvent when applied to form the release layer. The solvent is not particularly limited, and examples thereof include: hydrocarbon solvents such as n-hexane, cyclohexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and organic solvents such as alcohol solvents such as methanol, ethanol, and butanol.

[0132] The release agent can be applied by a micro gravure coater, a gravure coater, or the like. The release agent can be applied in a solid content of 0.1 g / m 2 ~2.0g / m 2 , preferably 0.5g / m 2 ~1.2g / m 2 The coating is applied in a left-right manner and cured to provide a release layer.

[0133] As a hardening method, in order to simply promote hardening, thermal hardening is preferred. As a hardening temperature, there is no particular limitation, but it is preferably 80°C to 130°C. If it is above 80°C, long-term heating is not required for sufficient hardening, and productivity is improved. In addition, if it is below 130°C, the generation of wrinkles caused by heat can be reduced in the substrate or the peeling substrate. The thickness of the release layer is not particularly limited. For example, it is about 0.1μm to 2μm.

[0134] 4. Manufacturing of double-sided adhesive sheets

[0135] The double-sided adhesive sheet of the present disclosure can be manufactured by a known method. For example, an adhesive composition can be applied to a second release sheet and coated, and the adhesive layer can be hardened to form an adhesive layer, and a first release sheet can be attached to one of the exposed surfaces of the adhesive layer to manufacture the double-sided adhesive sheet. Then, the obtained double-sided adhesive sheet can be rolled into a roll to obtain a roll sheet.

[0136] The coating can be carried out, for example, by a micro gravure coater, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a rod blade coater, a knife coater, a spray coater, a die coater, or a curtain coater. In the case where the adhesive composition contains a solvent, after coating, the solvent is removed by a drying process. Hardening is hardened, for example, by aging. In the case of a light-curing adhesive composition, it is hardened by irradiating ultraviolet light (ultraviolet, UV) and the like.

[0137] After manufacturing the double-sided adhesive sheet, or while manufacturing the double-sided adhesive sheet, the double-sided adhesive sheet is wound in a roll shape on a reel, thereby obtaining a double-sided adhesive sheet roll. The length of the roll can be designed according to the purpose. From the perspective of improving productivity, it is preferably more than 50m, and more preferably more than 100m. From the perspective of manufacturing yield, the length of the roll is preferably set to less than 2500m.

[0138] Alternatively, the manufacturing method may be performed by applying an adhesive layer to the release surfaces of the first release sheet and the second release sheet so that the thickness after drying becomes a predetermined thickness, thereby forming two adhesive layers respectively, and then attaching the adhesive layers.

[0139] 5. Laminated body for image display device

[0140] In the laminated body for image display device disclosed in the present invention, adherends are bonded to each other via the adhesive layer of the double-sided adhesive sheet. The laminated body for image display device is formed using a double-sided adhesive sheet without a substrate that can suppress wrinkles and bubbles even when applied to a flexible display, and is therefore suitable for optical elements such as liquid crystal elements and organic electroluminescence (EL) elements that require visibility. A flexible display is a display that can be bent, such as an organic electroluminescence (organic EL) display, an electrophoretic display (electronic paper), a liquid crystal display using a plastic substrate (film) as a substrate, and a foldable display that can be folded.

[0141] The adhesive layer formed by the adhesive sheet is suitable for bonding bendable components (adherends) to each other, for example, it is suitable for bonding components of any combination of liquid crystal polymer sheets, light-emitting polymer sheets, sheet-like liquid crystal modules, organic EL modules (organic EL sheets), electronic paper modules, transparent conductive sheets, metal mesh sheets, sheet sensors, cover sheets, barrier films, polarizing films, polarizers, phase difference films, viewing angle compensation films, brightness enhancement films, contrast enhancement films, diffusion films, semi-transmitting reflective films, and electrode films.

[0142] [Example]

[0143] Hereinafter, the present disclosure will be described in more detail based on the examples. However, the present disclosure is not limited thereto. Unless otherwise specified, the "parts" in the examples represent "parts by mass" and "%" represents "% by mass". Blank columns in the table represent that no blending is performed.

[0144] (a) Determination method

[0145] The numerical values ​​determined in this example are values ​​obtained by the following method.

[0146] a-1. Tg of (meth)acrylic acid copolymer (a)

[0147] The Tg of the adhesive resin was measured using a robot DSC (differential scanning calorimeter, "RDC220" manufactured by Seiko Instruments). About 2 mg of the sample was placed in an aluminum pan, weighed, and placed in the differential scanning calorimeter. The same type of aluminum pan without the sample was used as a reference, and after being kept at 100°C for 5 minutes, liquid nitrogen was used to quench to -120°C. Thereafter, the temperature was raised at a rate of 5°C / min, and the Tg (°C) of the adhesive resin was determined from the obtained DSC chart.

[0148] a-2. Tg of adhesive layer

[0149] The first peeling sheet and the second peeling sheet were peeled off from the double-sided adhesive sheets of each embodiment and comparative example manufactured by the method described below, and 2 mg of the adhesive layer was placed in an aluminum pan, weighed, and set in a differential scanning calorimeter. The same type of aluminum pan without the sample was used as a reference, and after being kept at 100° C. for 5 minutes, liquid nitrogen was used to quench to -120° C. Thereafter, the temperature was raised at a rate of 5° C. / min, and the Tg (° C.) of the adhesive resin was determined based on the obtained DSC chart.

[0150] a-3. Weight average molecular weight Mw and molecular weight dispersion Mw / Mn of adhesive resin

[0151] Mw was measured using a gel permeation chromatograph (GPC) "LC-GPC system" manufactured by Shimadzu Corporation, and Mw and molecular weight dispersion Mw / Mn were calculated by conversion using polystyrene of known molecular weight as a standard substance.

[0152] Device name: LC-GPC system "Prominence" manufactured by Shimadzu Corporation

[0153] Pipe string: Four GMHXL pipes manufactured by Tosoh and one HXL-H pipe manufactured by Tosoh are connected.

[0154] Mobile phase solvent: tetrahydrofuran

[0155] Flow rate: 1.0mL / min

[0156] Column temperature: 40℃

[0157] a-4. Thickness Tt of double-sided adhesive sheet, thickness Ta of adhesive layer, thickness Tl of first release sheet, thickness Th of second release sheet

[0158] From the end of the width direction of the double-sided adhesive sheet (first peeling sheet / adhesive layer / second peeling sheet) to the other end, 10 positions at equal intervals are determined, and the thickness of the 10 positions is measured, and its average value is set to Tt. In addition, the so-called end refers to the end of the area stacked with the first peeling sheet / adhesive layer / second peeling sheet. Then, the first peeling sheet is peeled off from the double-sided adhesive sheet, and the thickness of the first peeling sheet peeled off at 10 positions corresponding to the same position is measured. Its average value is set to Tl. Thereafter, the second peeling sheet is peeled off from the adhesive layer, and the thickness of the second peeling sheet peeled off at 10 positions corresponding to the same position is measured. Its average value is set to Th. The thickness Ta of the adhesive layer is obtained by Tt-Tl-Th.

[0159] In addition, for the reference example 1 described later, the thickness Tt of the single-sided adhesive sheet is measured in the same manner as the double-sided adhesive sheet, the thickness Tl of the release sheet is measured in the same manner as the first release sheet, and the thickness Th of the base film is measured in the same manner as the second release sheet by removing the adhesive layer from the base film using an arbitrary solvent.

[0160] a-5. Measurement of Reflection Intensity Wa to Reflection Intensity We of Adhesive Layer

[0161] A glass plate (blue plate glass, manufactured by Kawamura Hisazo Shoten Co., Ltd.) with a width of 200 mm, a length of 120 mm, and a thickness of 1.1 mm was attached to the surface of the adhesive layer exposed by peeling off the first peeling sheet of a double-sided adhesive sheet cut into a width of 20 mm and a length of 200 mm, and the glass plate was placed on a thick white drawing paper (P156J, manufactured by JOINTEX) to prepare a measurement sample. The surface of the adhesive layer exposed by peeling off the second peeling sheet of the measurement sample was scanned for more than 150 mm in the longitudinal direction using a waveform scanning device (manufactured by BYK Gardner, waveform scanning 3 dual), thereby measuring Wa to We.

[0162] In addition, about Reference Example 1, the measurement was performed by the same method as Example 1 except that the film substrate was placed on the glass plate having a thickness of 1 mm, and the glass plate was placed on the white drawing paper (thick) to prepare a measurement sample.

[0163] a-6. Determination of solid content

[0164] The mass (W0) of the aluminum cup is measured using a precision balance. Next, about 1 g of the sample solution is placed in the aluminum cup, and the mass (W1) of the sample placed in the aluminum cup is measured using a precision balance. After the sample placed in the aluminum cup is heated in an oven at 150°C for 2 hours, it is taken out of the oven and returned to room temperature. The residual mass (W2) of the heated sample placed in the aluminum cup is measured using a precision balance. Then, the solid content is calculated using the formula (W2-W0) / (W1-W0)×100(%).

[0165] a-7. Storage elastic modulus

[0166] Prepare two groups of sheets after peeling off the first release sheet of the double-sided adhesive sheet, use a laminator to stick the adhesive layers to each other, and make a laminate of the second release sheet / adhesive layer / second release sheet. Peel off the second release sheet on one side of the laminate, and stick the adhesive layers in sequence to form a laminate of an adhesive layer with a thickness of 1 mm. For the laminate, use a rheometer (manufactured by TA Instruments, DHR-2) using a φ8mm measuring probe to measure the storage elastic modulus G' under the conditions of strain 0.1%, frequency 1Hz, and a heating rate of 10°C / minute from -70°C to 200°C. Read the measured values ​​for each temperature of 0°C, 23°C, and 40°C from the obtained data.

[0167] a-8. Determination of gel fraction

[0168] The double-sided adhesive sheet was cut into a size of 30 mm × 100 mm, and the adhesive layer exposed by peeling off the first peeling sheet was attached to a weighed 300-mesh stainless steel wire mesh (mass W0), and the second peeling sheet was peeled off to obtain a sample. The mass obtained by weighing the sample was set as W1. Then, the sample was allowed to stand in ethyl acetate for 24 hours and dried at 100°C for 1 hour. Then, the mass obtained by weighing was set as W2. The gel fraction was calculated by the following formula.

[0169] Gel fraction (%) = {(W2-W0) / (W1-W0)}×100

[0170] (b) Production Example of (meth)acrylic acid copolymer (a)

[0171] b-1. (Meth)acrylic acid copolymer (R1)

[0172] In a reaction vessel (hereinafter simply referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, a dropping device, and a nitrogen introduction tube, 80 parts of ethyl acetate (EtAc), 30 parts of butyl acrylate (BA), 35 parts of 2-ethylhexyl acrylate (2EHA), 30 parts of isobornyl acrylate (IBXA), 5 parts of 4-hydroxybutyl acrylate (4HBA), and 0.1 parts of 2,2'-azobisisobutyronitrile (hereinafter simply referred to as "AIBN") as an initiator were placed, and the atmosphere in the reaction vessel was replaced with nitrogen. Thereafter, the reaction was started by heating to 65°C while stirring under a nitrogen atmosphere. Thereafter, the reaction solution was reacted at 65°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate (EtAc) to obtain a (meth)acrylic acid copolymer (R1) solution having a solid content of 50%. The obtained copolymer (R1) had an Mw of 1,000,000 and a Tg of -39°C.

[0173] (Meth)acrylic acid copolymers (R2 to R7) were produced by the same method as that for producing the (meth)acrylic acid copolymer (R1), except that the composition and the blending amount (parts by mass) were changed to those shown in Table 1.

[0174] [Table 1]

[0175]

[0176] The abbreviations in the table are as follows.

[0177] (chain or branched (meth)acrylic acid alkyl ester monomer)

[0178] MA: Methyl acrylate (the carbon number of the alkyl group is 1)

[0179] BA: n-butyl acrylate (alkyl carbon number 4)

[0180] 2EHA: 2-ethylhexyl acrylate (alkyl carbon number 8)

[0181] 2EHMA: 2-ethylhexyl methacrylate (alkyl carbon number 8)

[0182] DOA: dodecyl acrylate (alkyl carbon number 12)

[0183] (Other single bodies)

[0184] IBXA: Isobornyl acrylate

[0185] CHA: Cyclohexyl acrylate

[0186] AA: Acrylic acid

[0187] 4HBA: 4-Hydroxybutyl acrylate

[0188] (c) Preparation of adhesive composition

[0189] c-1. Production of Adhesive Composition C1

[0190] With respect to 100 parts of the solid content of the (meth)acrylic copolymer (R1), 0.1 parts of xylylene diisocyanate (XDI) (Takenate D-110N, manufactured by Mitsui Chemicals, Inc.) as a curing agent, 0.1 parts of a silane coupling agent (KBM-303, manufactured by Shin-Etsu Silicone Co., Ltd.) as an additive were mixed, and ethyl acetate (EtAc) was further mixed so that the solid content became 25%, and stirred to obtain an adhesive composition C1.

[0191] c-2. Production of Adhesive Compositions C2 to C11

[0192] Adhesive compositions C2 to C11 were obtained by the same method as that of adhesive composition C1 except that the types of (meth)acrylic copolymer, curing agent and additives were changed as shown in Table 2. In addition, regarding C3, the solid content was appropriately adjusted according to the Examples described below.

[0193] [Table 2]

[0194]

[0195] The abbreviations in the table are as follows.

[0196] (Hardener)

[0197] XDI: Xylene diisocyanate (Takenate D-110N, manufactured by Mitsui Chemicals)

[0198] TDI: Toluene diisocyanate (Cosmonate T100, manufactured by Mitsui Chemicals Fine Chemicals Co., Ltd.)

[0199] HDI: Hexamethylene diisocyanate (adduct of trimethylolpropane) (Takenate D-160N, manufactured by Mitsui Chemicals, Inc.)

[0200] EP: Epoxy hardener (E-5XM, manufactured by Soken Chemical Co., Ltd.)

[0201] SC: Silane coupling agent (KBM-303, manufactured by Shin-Etsu Silicone Co., Ltd.)

[0202] TF: Thickener (D-125, manufactured by Arakawa Chemical Industries, Ltd.)

[0203] (d) Production Example of Double-Sided Adhesive Sheet

[0204] d-1. Example 1

[0205] Adhesive composition C1 is applied on the release layer of the second release sheet (heavy release polyethylene terephthalate separator) with a thickness of 75 μm and a width of 30 cm at a speed of 10 m / min, and dried in a hot air oven at 120 ° C for 2 minutes to form an adhesive layer. Then, a double-sided adhesive sheet is made by laminating the release layer of the first release sheet (light release polyethylene terephthalate separator) with a thickness of 50 μm and a width of 30 cm on the adhesive layer. The obtained double-sided adhesive sheet is wound with a tension of 50 N for a length of 50 m while not wrinkling the acrylonitrile-butadiene-styrene (ABS) core with a diameter of 3 inches, thereby making a roll-shaped double-sided adhesive sheet. The roll-shaped double-sided adhesive sheet made is aged for one week at a temperature of 40 ° C and a relative humidity of 50%. Thereafter, the roll was unwound from the outwardly wound side, and the roll was unwound by 50 cm in the longitudinal direction starting from the position where the roll was unwound by 5 m, and the roll was cut to obtain an outwardly wound double-sided adhesive sheet of 30 cm in width and 50 cm in the longitudinal direction.

[0206] The double-sided adhesive sheet was cut out to 50 cm in length from the end of the double-sided adhesive sheet on the inner roll side (core side) of the roll to the outer roll side to obtain an inner roll double-sided adhesive sheet of 30 cm in width and 50 cm in length.

[0207] d-2. Example 2 to Example 35, Comparative Example 1 to Comparative Example 6

[0208] Double-sided adhesive sheets of Examples 2 to 35 and Comparative Examples 1 to 6 were obtained in the same manner as in Example 1 except that the adhesive compositions and coating conditions described in Tables 3 to 5 were changed.

[0209] d-3. Reference Example 1

[0210] Adhesive composition C9 was applied to the release layer of a 75 μm thick and 30 cm wide release film (manufactured by Toray Film Processing Co., Ltd., BX8A) at a speed of 10 m / min in such a way that the thickness after drying became 50 μm and the width was 20 cm, and the adhesive layer was dried in a hot air oven at 120 ° C for two minutes, thereby forming an adhesive layer. Then, a single-sided adhesive sheet was made by laminating a film substrate (manufactured by Toray, U403) with a thickness of 23 μm and a width of 30 cm to the adhesive layer. The obtained single-sided adhesive sheet with a substrate was wound up with a tension of 50 N for 50 m while paying attention to not wrinkling the ABS core with a diameter of 3 inches, thereby making a roll-shaped single-sided adhesive sheet. The produced roll-shaped single-sided adhesive sheet was aged for one week at a temperature of 40 ° C and a relative humidity of 50%. Thereafter, the single-sided adhesive sheet for outer roll and the single-sided adhesive sheet for inner roll were obtained by the same method as in Example 1.

[0211] (e) Evaluation of double-sided adhesive sheets, etc.

[0212] The double-sided adhesive sheets of each example and comparative example and the single-sided adhesive sheet of the reference example were evaluated as follows. The results are shown in Tables 3 to 5. In the examples and comparative examples, the first release sheet is a so-called light release sheet, and the second release sheet is a so-called heavy release sheet.

[0213] e-1. Evaluation of visibility

[0214] The double-sided adhesive sheet rolled out of each embodiment and comparative example is cut into 80mm×40mm, and the first peeling sheet is peeled off and attached to the glass plate. Furthermore, the second peeling sheet is peeled off and attached to the organic EL module (manufactured by TEIDEC, REC001602A-W) to make a display. In the display, white text (uppercase letters A to P, lowercase letters a to p, a total of 32 letters) is displayed on a black background and is set on a horizontal table. The observer observes the display light from three angles: an angle of 30° rising from the horizontal direction, an angle of 45° rising, and a vertical angle of 90° rising. The observer visually compares and evaluates the deformation and blurring of the image displayed on the display before and after the double-sided adhesive sheet is attached.

[0215] Reference Example 1 was evaluated in the same manner as in Example 1 except that the release sheet was peeled off and attached to an organic EL module (REC001602A-W manufactured by TEIDEC) and a glass plate was placed on the base film to prepare a display.

[0216] The evaluation criteria are as follows: 3 or more is good, and 2 is practical.

[0217] 5: No deformation or blurring of the outline is observed at any angle.

[0218] 4: Slight distortion and / or blurring of the outline is visible at any angle.

[0219] 3: Slight distortion and / or blurring of the outline is visible at any two angles.

[0220] 2: Slight distortion and / or blurring of the outline is visible at all angles, but is not a problem in practical use.

[0221] 1: At more than one angle, distortion and / or smudging of the outlines is more than a little visible, making it difficult to discern multiple letters.

[0222] In the above description, the term “a small number” means that the number of letters that are difficult to distinguish due to deformation and shading of the outline is 2 or less among the 32 letters.

[0223] e-2. Evaluation of bubbles and wrinkles (roller)

[0224] An arbitrary portion of the inwardly rolled double-sided adhesive sheet of each example, comparative example, and reference example was cut into four 10 cm square pieces, and the presence of bubbles and wrinkles derived from roll storage was visually observed.

[0225] The evaluation criteria are as follows: 3 or more is good, and 2 is practical.

[0226] 5: No bubbles or wrinkles larger than 1 mm were observed in all 4 double-sided adhesive sheets.

[0227] 4: No bubbles or wrinkles larger than 1 mm were found in the 3 double-sided adhesive sheets.

[0228] 3: No bubbles or wrinkles larger than 1 mm were found in the two double-sided adhesive sheets.

[0229] 2: No bubbles or wrinkles larger than 1 mm were found in a double-sided adhesive sheet.

[0230] 1: Bubbles and wrinkles larger than 1 mm were found in all double-sided adhesive sheets.

[0231] e-3. Evaluation of bubbles and wrinkles (folds)

[0232] The first release sheet was peeled off from the outwardly wound double-sided adhesive sheet of each example and comparative example, and the exposed adhesive layer was laminated on the polyimide film.

[0233] Next, the second release sheet was peeled off from the adhesive layer, and the exposed adhesive layer was laminated on an easily bonded polyethylene terephthalate (PET) film. The laminate was placed in an autoclave and kept at 50°C for 20 minutes. Next, the laminate was taken out and left to stand at 25°C and 50% RH for 30 minutes, and then cut into a size of 70 mm wide and 100 mm long, thereby obtaining a test laminate comprising an easily bonded PET film / adhesive layer / polyimide.

[0234] Next, the test laminate was bent using a planar body unloaded torsion tester (manufactured by YUASASYSTEM) in an atmosphere of 23°C and 50% RH, and the cycle was repeated for 200,000 cycles until the state before bending was restored. The test was conducted with N=5, and the appearance after the test was evaluated visually. With respect to Reference Example 1, the same method as in Example 1 was used for evaluation except that the peeling sheet was peeled off to obtain an adhesive layer with a film substrate, and the exposed adhesive layer was laminated on a polyimide film. The evaluation criteria are as follows.

[0235] 5: No bubbles or wrinkles were observed in all 5 samples.

[0236] 4: Bubbles and / or wrinkles were visible in 1 sample.

[0237] 3: Bubbles and / or wrinkles were visible in 2 samples.

[0238] 2: Bubbles and / or wrinkles were visible in 3 samples.

[0239] 1: Bubbles and / or wrinkles are visible in 4 or all samples.

[0240] The evaluation of bubbles and wrinkles (folds) was performed in the same manner except that the temperature was changed from 23°C to 0°C and 40°C, respectively. The evaluation criteria were the same as those at 23°C.

[0241] [Table 3]

[0242]

[0243] [Table 4]

[0244]

[0245] [Table 5]

[0246]

[0247] As for the double-sided adhesive sheet that does not satisfy the reflection intensity Wa of 1 to 26 and the reflection intensity Wd of 0.3 to 8, as shown in Comparative Examples 1 to 4, the visibility is reduced and the problem is confirmed in bubbles and wrinkles. In addition, as for the double-sided adhesive sheet that satisfies the reflection intensity Wa of 1 to 26 and the reflection intensity Wd of 0.3 to 8, but the adhesive layer does not satisfy the above (i) to (iii), as shown in Comparative Examples 5 to 6, the problem is confirmed in bubbles and wrinkles (folds). In contrast, as for the double-sided adhesive sheet that satisfies the reflection intensity Wa of 1 to 26 and the reflection intensity Wd of 0.3 to 8, and the adhesive layer satisfies the above (i) to (iii), as shown in Examples 1 to 35, the visibility is excellent and wrinkles and bubbles can be suppressed.

Claims

1. A double-sided adhesive sheet for use in a substrate-free flexible display, which is formed by laminating a first release sheet, an adhesive layer, and a second release sheet in this order, wherein: When a glass substrate is attached to the surface of the adhesive layer exposed by peeling off the first peeling sheet and the glass substrate is placed on a white paper, the surface of the adhesive layer exposed by peeling off the second peeling sheet is measured by a waveform scanning device. The reflection intensity Wa in the wavelength range of 0.1 mm to 0.3 mm is 1 to 26, and The reflection intensity Wd in the wavelength range of 3mm to 10mm is 0.3 to 8. Regarding the adhesive layer, (i) is any one of an adhesive layer containing a (meth)acrylic copolymer (a) having a weight average molecular weight of 1,000,000 to 1,800,000, and an adhesive layer obtained by crosslinking an adhesive composition containing a (meth)acrylic copolymer (a), (ii) The storage elastic modulus at 23°C is 1×10 3 Pa~8×10 4 Pa, (iii) The glass transition temperature determined by differential scanning calorimetry is -70°C ≤ Tg ≤ -35°C.

2. The double-sided adhesive sheet according to claim 1, wherein When a glass substrate is attached to the surface of the adhesive layer exposed by peeling off the first peeling sheet and the glass substrate is placed on a white paper, the surface of the adhesive layer exposed by peeling off the second peeling sheet is measured by a waveform scanning device. The reflection intensity Wc in the wavelength range of 1mm to 3mm is 1 to 12, and The reflection intensity We in the wavelength range of 10 mm to 30 mm is 1 to 12.

3. The double-sided adhesive sheet according to claim 1, wherein The (meth)acrylic acid copolymer (a) has a structural unit derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 6 carbon atoms, and a structural unit derived from a linear or branched (meth)acrylic acid alkyl ester monomer having an alkyl group with 7 to 12 carbon atoms.

4. The double-sided adhesive sheet according to claim 1, wherein The molecular weight distribution Mw / Mn of the (meth)acrylic acid copolymer (a) is less than 5. 5 . A laminate for an image display device, wherein adherends are bonded together via the adhesive layer of the double-sided adhesive sheet according to claim 1 .

Citation Information

Patent Citations

  • Adhesive, adhesive sheet and display

    JP2013127012A

  • Adhesive composition, adhesive sheet and optical laminated sheet

    JP2014074122A

  • Adhesive composition and adhesive sheet

    JP2016079266A

  • Adhesive composition and adhesive sheet

    JP2016188309A

  • Pressure sensitive adhesive composition

    JP2018002961A